In thy light - Kanal, Parasram Verhomal, 1883- (Dev Samaj Publications, 1979)
Letters of a devotee to his guru, Dev Atma (Satyanand Agnihotri, 1850-1929) who seceded from the Brahmo Samaj and founded the Dev Samaj, a parallel Hindu socio-religious society.